2005
DOI: 10.1002/mrd.20379
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor system in the cow oviduct: A possible involvement in the regulation of oviductal motility and embryo transport

Abstract: Vascular endothelial growth factor (VEGF) is a potent angiogenic and permeability enhancing factor, which shows the highest activity in the oviduct during the periovulatory period of the estrous cycle in cattle. It has also been shown that the contraction activity of oviduct is highest during the periovulatory period. The present study therefore focused on the possible involvement of VEGF in the regulation of biosynthesis and secretion of contraction-relaxation-related substances in the cow oviduct. Possible a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 33 publications
4
55
0
3
Order By: Relevance
“…The lack of significant elevation of the ACE-1 mRNA level when Ang II release is increased during the follicular phase is difficult to explain; however, it has been reported that E2 induces hepatic angiotensinogen synthesis and release [26,27] and that the plasma rennin concentration is higher during estrus [28] in rats. Thus, the elevated precursor levels in the oviducts coincident with the elevated systemic E2 levels during the follicular phase could be attributed to increased Ang II release without significant rise in the ACE-1 mRNA level.Previously, we have shown that LH activates a system of various vasoactive peptides in the bovine oviduct, including ET-1 [8], vascular endothelial growth factor (VEGF) [29] and tumor necrosis factor α (TNFα) [7,8]. In the present study, we also observed that LH upregulates ACE-1 mRNA expression in cultured OECs and that LH stimulates the release of Ang II in both microdialysis and cell culture.…”
supporting
confidence: 75%
“…The lack of significant elevation of the ACE-1 mRNA level when Ang II release is increased during the follicular phase is difficult to explain; however, it has been reported that E2 induces hepatic angiotensinogen synthesis and release [26,27] and that the plasma rennin concentration is higher during estrus [28] in rats. Thus, the elevated precursor levels in the oviducts coincident with the elevated systemic E2 levels during the follicular phase could be attributed to increased Ang II release without significant rise in the ACE-1 mRNA level.Previously, we have shown that LH activates a system of various vasoactive peptides in the bovine oviduct, including ET-1 [8], vascular endothelial growth factor (VEGF) [29] and tumor necrosis factor α (TNFα) [7,8]. In the present study, we also observed that LH upregulates ACE-1 mRNA expression in cultured OECs and that LH stimulates the release of Ang II in both microdialysis and cell culture.…”
supporting
confidence: 75%
“…The local content of VEGF in the bovine oviduct is at its highest during the periovulatory period [8], and may be responsible for the higher fluid secretion within the oviduct during this period [24]. Moreover, we recently reported that VEGF may contribute to regulation of the different contractile patterns of the oviduct, which occur during the period of gamete and embryo transport [15]. TNFα and its receptors are highly expressed in the cow oviduct during the periovulatory period, and may act to optimize the release of contraction-related substances during this period [13].…”
Section: Discussionmentioning
confidence: 98%
“…I n t h e f e m a l e r e p r o d u c t i v e s y s t e m , t h e appropriate biological activity of VEGF and TNFα are crucial for the cascade of events that produce a successful pregnancy [8,13,15,[21][22][23]. The local content of VEGF in the bovine oviduct is at its highest during the periovulatory period [8], and may be responsible for the higher fluid secretion within the oviduct during this period [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This downregulation was further intensified in the presence of LH (Wijayagunawardane et al, 2005). The periovulatory stage was associated with the highest contraction acitivity of the oviduct and the LH-VEGF interrelation might regulate oviductual contraction to assure an optimal transport of the oocyte through the oviduct by regulation contraction.…”
Section: The Impact Of Lh On Blood Vessel and Oviduct Physiologymentioning
confidence: 95%